Bureaucracy of Power and of the Power Bureaucracy: Review on the Collection of Essays by V.P. Makarenko - S. S. Neretina (Сравнительная политика, 2020)
Review of the books: Makarenko, V.P. Sobr. soch.: v 3-kh t. [Coll. cit .: in 3 volumes]. Rostov-on-Don; Taganrog: Southern Federal University Publishing House, 2019. This is the review of the three-volume book by V.P. Makarenko, the author of over 500 works, Doctor of Philosophy and Political Sciences, Professor, Honored Scientist of the Russian Federa-tion, Academician of the Academy of Pedagogical Sciences of Ukraine, Chief Researcher, Head of the Center for Political Conceptology of the Institute of Philosophy, Social and Political Sciences of the Southern Federal university. This is the work of a person who devoted his life to the study of socio-political processes taking place before his eyes, which required understanding from the point of view of time, history, and civilization. This collection comprises essays written from 1980s to 2010s. The author included them to illus-trate his cross-cutting idea of the relationship between power, bureaucracy and society. The au-thor's successes and failures are also noted. V.P. Makarenko understands bureaucracy as a ‘trans-formed form of expression of universal interests’, a social organism-parasite throughout its his-torical existence, reflection of social contradictions and conflicts, materialization of political and managerial alienation. The methodological thought of Makarenko is devoted to the explanation of this phenomenon, whose task is to develop his own concept and destroy long-term myths about bureaucracy as an example of ‘rational management of society’. Makarenko proceeds from the difference between name and description and on this basis de-scribes bureaucratic ontology, epistemology and axiology. V.P. Makarenko's concept of bureau-cracy can be understood as a version of a theory that can fall under the status of error (according to K. Popper's theory). It implies the transformation of the common good as an ideal idea into an embodied common evil, a particular case of which is civilization and any power. The errors of various theories of state structures, relations and power are also described. The bureaucratic state created by Lenin and Stalin is a formally developed system of total lies, the consequences and incarnations of which still exist in Russia.